PERENCANAAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) PABRIK TEMPE DENGAN DIGESTER ANAEROBIK DAN BIOFILTER ANAEROBIK DI WILAYAH SEMARANG (Studi Kasus Pabrik Tempe Dampyak Gunung Pati Kota Semarang) - Rizani, Mohammad Debby; Ikhwanudin, Ikhwanudin; Lestiyanto, Yoga; Anggraeni, Yossi Dewi (Jurnal Teknik Sipil Giratory UPGRIS, 2023)
The tempe industry is a food industry that has the potential to pollute the environment from the liquid waste it produces. Liquid waste from the tempe processing process if it is immediately disposed of without going through the management process first will have an impact on environmental pollution. In Semarang City, precisely in Gunung Pati District, there is a medium-scale tempe processing factory. So far, the tempe factory's liquid waste is directly disposed of into a ditch behind the factory without processing the liquid waste first.This research is a quantitative research presented in the form of numbers and then explained in the form of descriptions. From the results of the wastewater quality test, the pollutant parameters BOD = 369 mg/L; COD = 28,000 mg/L; TSS = 0.991 mg/L; and pH = 4,3. According to the Regional Regulation of the Province of Central Java Number 5 of 2012 concerning Amendments to the Regional Regulation of the Province of Central Java Number 10 of 2004 this value still does not meet the requirements. The wastewater treatment plant that the researchers are planning is in the form of a holding tank; Equalization Tub; Anaerobic Digesters; Gas Holder; Initial Settling Tub; Anaerobic Biofilter using bioball filter media and steel nets as a barrier for bioballs where bacteria are grown; and Final Settling Tank. With an estimated effluent from the processing of BOD, COD, and TSS of 7.47225 mg/L; 189mg/L; and 0.00669 mg/L which means it meets the quality standard. From the planning results, it was obtained that the total budget plan for planning the tempe factory wastewater treatment plant was Rp. 111.280.021,49.